2011
DOI: 10.1590/s1413-81232011000600020
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de salud en Colombia: 20 años de logros y problemas

Abstract: Sistema de salud en Colombia: 20 años de logros y problemasThe Colombian healthcare system: 20 years of achievements and problemsResumen Se presenta un balance de algunos procesos claves y resultados del Sistema General de Seguridad Social en Salud (SGSSS) en Colombia. Se realizó una revisión sistemática de literatura publicada en revistas indexadas con valoración de la calidad de la evidencia, y literatura no publicada en revistas. Los recursos financieros del sistema de salud, se han incrementado de manera s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 9 publications
0
30
0
21
Order By: Relevance
“…Other authors have reported that younger women have reduced probabilities of having Pap test [14,16,25,31,32], especially if residing in rural areas [14]. Although better coverage of subsidised health insurance in rural areas has been reported in Colombia [21], people with subsidised health insurance receive 40% less health care compared to those with contributory health insurance [21]. In this regard, our results also show that women in rural areas with subsidised insurance have a lower probability of having had a Pap test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported that younger women have reduced probabilities of having Pap test [14,16,25,31,32], especially if residing in rural areas [14]. Although better coverage of subsidised health insurance in rural areas has been reported in Colombia [21], people with subsidised health insurance receive 40% less health care compared to those with contributory health insurance [21]. In this regard, our results also show that women in rural areas with subsidised insurance have a lower probability of having had a Pap test.…”
Section: Discussionmentioning
confidence: 99%
“…Public teachers and universities workers, members of the military forces, police, and employees of the Colombian Oil Company have special health insurance plans [18]. Differences in access to health care benefits between the contributory and subsidised systems have been reported [19][20][21] which mainly affect disadvantaged populations [19,22,23]. The SGSSS has been criticised for not considering geographical, social, and cultural contexts, increasing barriers to access health care [24].…”
mentioning
confidence: 99%
“…According to the Overall Performance Report by the World Health Organization (2000), which compares the National Health Systems, Colombia was in 22nd place in health system performance (World Health Organization). Important health reforms introduced in Colombia has increased the number of insured people to the system; nevertheless, this situation did not guarantee an equitable access to the different preventive and curative programs within the different levels of oral health care (Calderón et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health loose priority is evident when seeking oral professional care only in cases of true dental/oral emergencies. Economic barriers (Calderón et al, 2011) are an important issue due firstly to the cost of commuting to the health center (in this case is associated to geographic barriers) and secondly to the need of payment for a percentage of total service (copayment). It is important to mention that an important part of the Colombian population live in poverty and indigence (Colombia Líder -Fedesarrollo, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Desde la implementación del Sistema General de Seguridad Social en Salud en el año 1993, y sus posteriores reformas, se han asentado muchas críticas debido principalmente al hecho de que a pesar de que la cobertura en salud aumentó (incremento en el número de personas afiliadas al sistema), se han presentado barreras de acceso a los servicios de salud por limitaciones en los planes de beneficio o por dificultades administrativas, entre otras causas (20). Aunque se han realizado investigaciones que tratan de identificar determinantes que afectan el acceso y la utilización de los servicios de salud (21,22), estudios enfocados en analizar el acceso a los servicios de salud bucal, concretamente, son más escasos en el país, y mucho menos en población adulta mayor (23,24).…”
Section: Introductionunclassified